Aggregatibacter actinomycetemcomitans and Filifactor alocis: Two exotoxin-producing oral pathogens - Ozuna, Hazel; Snider, Ian; Belibasakis, Georgios N.; Oscarsson, Jan; Johansson, Anders; Uriarte, Silvia M. (Frontiers in Oral Health, 2022)
Periodontitis is a dysbiotic disease caused by the interplay between the microbial ecosystem present in the disease with the dysregulated host immune response. The disease-associated microbial community is formed by the presence of established oral pathogens like Aggregatibacter actinomycetemcomitans as well as by newly dominant species like Filifactor alocis. These two oral pathogens prevail and grow within the periodontal pocket which highlights their ability to evade the host immune response. This review focuses on the virulence factors and potential pathogenicity of both oral pathogens in periodontitis, accentuating the recent description of F. alocis virulence factors, including the presence of an exotoxin, and comparing them with the defined factors associated with A. actinomycetemcomitans. In the disease setting, possible synergistic and/or mutualistic interactions among both oral pathogens might contribute to disease progression.